Towards sustainable data centres: Novel internal network technologies leading to sustainable cost and energy consumption in data centres in The Netherlands - Bob van den Berg; Bert M. Sadowski; Luuk Pals (International Telecommunications Society (ITS), 2018)
Information technology (IT), and in particular data centres, consume a huge amount of energy, which has negative influence on climate change. Therefore, it is important to look at the sustainability of data centres, especially in the Netherlands as one of the major location of these centres in Europe. In order to examine the extent to which data centres are sustainable and energy efficient, a comprehensive total cost of ownerships (TCO) analysis is undertaken to get better insights into the different costs components and technological opportunities for further reductions. Even if there are already a number of TCO studies on data centres, there have been none dealing with the effects of technological change on the networking part of data centres. However, this can be considered as a serious shortcoming of current research as technological change will have (cost-saving) effects on the networking part of data centres and data traffic will have an impact on the rack. After examining technological change by comparing different network technologies (ethernet, glass fibre, and plastic optical fiber (POF) in data centres, our TCO model studies improvements regarding costs, energy reduction, and improved sustainability of these three technologies. We conclude that the implementation of glass fibre or POF in a data centre can provide cost improvements amounting to about 1% per year. Looking at the energy consumption of the network part, a reduction of approximately 20% for glass fibre and 40% for POF can be reached. Therefore, the model demonstrated that changing current network technologies within the data centre will result in a decrease of energy consumption and total cost ownership.
Keywords: 330